Perinatal Outcomes among Women Identified by a Community Health Needs Assessment - Duryea, Elaine L.; Martin, Robert; McIntire, Donald; Spong, Catherine Y.; Nelson, David B. (American Journal of Perinatology, 2021)
Objective The aim of the study is to compare perinatal outcomes for women with greater social needs, as identified by the Community Health Needs Assessment, to those of women living in other areas of the county.Study Design This was a retrospective cohort study of pregnant women delivering at a large inner-city county hospital. Perinatal outcomes were analyzed for women living within a target area with substantial health disparities and social needs, and compared with those women living outside the target area. Statistical analysis included student's t-test, Chi square, and logistic regression.Results Between January 2015 and July 2020, 66,936 women delivered at Parkland hospital. Of these, 7,585 (11%) resided within the target area. These women were younger (26.8 ± 6.5 vs. 27.9 ± 6.4 years, p < 0.001), more likely to be black (37 vs. 13%, p < 0.001), and had a higher body mass index or BMI (33.3 ± 7.0 vs. 32.6 ± 6.4 kg/m2, p < 0.001). All women were likely to access prenatal care, with 7,320 (96.5%) in the target area and 57,677 (97.2%) outside the area attending at least one visit. Adverse perinatal outcomes were increased for women living within the target area, which persisted after adjustment for age, race, and BMI. This included an increased risk of preeclampsia (adjusted risk ratio [aRR] 1.1, 95% confidence interval or CI [1.03, 1.2]) and abruption (aRR 1.3, 95% CI [1.1, 1.7]), as well as preterm birth before both 34 weeks (aRR 1.3, 95% CI [1.2, 1.5]) and 28 weeks (aRR 1.3, 95% CI [1.02,1.7]). It follows that neonatal ICU admission (aRR 2.1, 95% CI [1.3, 3.4]) and neonatal death (aRR 1.2, 95% CI [1.1, 1.3]) were increased within the target area. Interestingly, rate of postpartum visit attendance was higher in the target area (57 vs. 48%), p < 0.001.Conclusion Even among vulnerable populations, women in areas with worse health disparities and social needs are at greater risk of adverse perinatal outcomes. Efforts to achieve health equity will need to address social disparities.Key Points
Keywords: perinatal outcomes; social determinants; health disparities; pregnancy; preterm birth; preeclampsia